The Oracles in an 11th-Century Armenian Manuscript (Yerevan, Matenadaran, No. 9650) - Erich Renhart (Mesrop Mashtots Institute of Ancient Manuscripts)
The Graz Armenian palimpsest (University Library no. 2058/2, a Georgian manuscript of the 10th century with an underlying Armenian text from around the year 800) contains 279 oracle sayings together with the text of the Gospel of John. Its readable part (229 oracles) was published in 2015. The present article offers the oracles of another Armenian manuscript which is kept at the Matenadaran in Yerevan: M9650, dating from the 11th century. Here again, the oracles are added to the verses of the Gospel of John. Having their place in the margins and sometimes in wonderfully designed cartouches, they are arranged in a unique way. We don’t know a similar page layout elsewhere. The Syriac corpus of the same genre offers the oracles embedded in the text of John (London, British Library, add. 17,119, 6th/7th centuries). We give here the Armenian text of the oracles found in M9650, an English translation, and a first comparison with the oracles of the Graz palimpsest. Juxtaposing the two texts, we find total uniformity on the one hand and considerable variation in the wording, the formation of text sections and their sequence on the other.
Keywords: Philology